Sonoelastrographic finding of Achilles tendon in patients with ankylosing spondylitis and acromegaly - Karatas, Ahmet; Artas, Hakan; Ugur, Kader; Koca, Suleyman Serdar (Aves, 2022)
Objectives: Achilles tendinopathy can be noticed in both acromegaly and ankylosing spondylitis (AS). Acromegaly patients presenting with tendinopathy findings may be confused with AS findings. In this study, sonoelastrographic findings of Achilles tendon are explored in patients with AS and acromegaly. Methods: 25 patients with AS, 30 patients with acromegaly, and 18 healthy controls were enrolled in the study. Achilles tendon was evaluated by sonoelastography in all the study participants. Results: The thickness of Achilles tendon in neutral positions was higher in acromegaly patients than those in AS patients. The sonoelastography measurement of Achilles tendon was increased in acromegaly patients when compared to the control group and AS patients. Conclusion: The thickness of Achilles tendon can increase in patients with acromegaly and AS. However, the sonoelastographic features of Achilles tendon can be similar in patients with AS and acromegaly.
Keywords: Acromegaly; ankylosing spondylitis; sonoelastography